The Effectiveness of Problem-Based Learning Model to Improve Problem Solving Skills and Concept Understanding in Acid Base Solution - Jundu, Ricardus; Jelatu, Silfanus; Jeramat, Eufrasia; Ningsi, Gabariela Purnama (Jurnal Pendidikan MIPA, 2023)
This research investigates the difference between learning acid base solution material using the PBL model and conventional learning regarding the conceptual understanding and problem-solving ability of grade XI students at Setia Bakti Ruteng senior high school. Three science classes from Grade XI at Setia Bakti Ruteng Senior High School comprised the 76 students who made up the study's population. The research sample, comprised of 56 students, was divided into two classes for the experiments: classes 1 and 2. Experiment class 1 was handled utilizing the PBL approach, and experiment class 2 was conducted using 5 M learning. The cluster random sampling method was used to select the sample. An essay examination was used to assess students' idea understanding, and their problem-solving ability was determined by examining their responses to the problem-solving essay test. The study's findings indicate that when conceptual comprehension and problem-solving skills are tested simultaneously in grade XI students at Setia Bakti Ruteng Senior High School, the PBL approach and conventional learning produce significantly different learning outcomes. Keywords: problem-based learning, concept understanding, problem-solving.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp161-171